There, Then Back There Again: A Personal Reflection on Environmental Responsibility While Traveling Abroad - STACY VARS (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2021)
In my personal journey essay, “There, Then Back There Again”, I combine personal reflection with travel writing to explore my own conflicted feelings about traveling. I love to travel and hope to one day be able to travel more than I have been able to thus far. It is in my recent trip to Ecuador to study abroad that I started to grapple with concerns about the impact my traveling could have on the communities and environments around me. I began noticing the economic conditions of various neighborhoods we traveled through, as well as learned about environmental impacts of human activities in the Amazon and Galapagos. Couple this with a sharp awareness of the growing ecotourism trade and I found myself looking at my surroundings differently. Even in the presence of stunning mountain vistas with soaring condors, sitting atop rushing waters winding its way to join the Amazon River, or watching sea lions walking down the boardwalk to find a prime sunning spot, Ecuador opened my eyes to look below the mundane tourist traps and see the bigger, more complicated relationships of nature and humans, politics and culture, capitalism and survival. Before Ecuador traveling was about personal enjoyment. After Ecuador, it’s about learning, growing beyond simple consumerism, and then sharing my journey with those who can’t go themselves.
Keywords: Travel Writing; Personal Reflection